Green Public Financing Model for the Sustainability of Leading Commodities in the Sebamban Transmigration Area - Muhammad Billy Wicaksana; Riki Satia Muharam (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study aims to develop a Green Public Financing Model to support the sustainability of leading commodities in the Sebamban transmigration area. Sustainable development in transmigration regions faces major challenges, particularly limited financing integration, weak institutional coordination, and insufficient alignment between development programs and environmental sustainability goals. This research adopts a qualitative descriptive approach using document analysis, policy review, and field observations to examine existing public financing mechanisms and institutional arrangements. The proposed model integrates multiple financing sources, including village funds, regional government budgets, corporate social responsibility (CSR), and green financing instruments, through coordinated governance and sustainability-oriented budgeting. The results indicate that fragmented financing practices reduce development effectiveness, whereas integrated green public financing enhances economic productivity, strengthens social empowerment, and supports environmental protection. The model emphasizes the Triple Bottom Line framework as the primary outcome, ensuring balanced economic, social, and environmental sustainability. This study contributes conceptually by offering a structured public financing model applicable to transmigration areas with leading commodities. The findings provide practical implications for policymakers in designing sustainable financing strategies that align public expenditure with long-term development and environmental objectives.